Ferrocene based organometallic gelators: a supramolecular synthon approach - Sahoo, Pathik; Puranik, Vedavati G.; Patra, A. K.; Sastry, P. U.; Dastidar, Parthasarathi (Soft Matter, 2011)
The supramolecular synthon namely primary ammonium dicarboxylate (PAD) synthon has been exploited to generate a new series of salt based low molecular weight gelators (LMWGs) derived from ferrocenedicarboxylic acid (FDCA) and primary amines Me-(CH2)(n)-NH2 (n = 3-15). While most of the salts are capable of forming gels with DMSO and DMF, nearly all of them show a tendency to form gels with at least one of the solvents studied. Structure property correlation based on single crystal and powder X-ray diffraction data in combination with optical-, scanning-, and transmission-electron microscopy reveals that the supramolecular synthon approach adopted herein for designing LMWGs is indeed useful and allows one to get an easy access to a new series of organometallic gelators.